2021
DOI: 10.1177/2325967120975751
|View full text |Cite
|
Sign up to set email alerts
|

Low Rate of Return to Preinjury Tegner Activity Level Among Recreational Athletes: Results at 1 Year After Primary ACL Reconstruction

Abstract: Background: There is limited information about the functional recovery and rate of return to preinjury levels of sports among recreational athletes after anterior cruciate ligament reconstruction (ACLR). Purpose: To investigate the recovery of quadriceps or hamstring strength, assess functional performance, and determine the rate of return to preinjury sports levels among recreational athletes at 1 year after ACLR. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 91 recreational-level athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The rate of return to sport is higher in athletes younger than 19 years, at all levels of participation 12 . Elite athletes show the highest rate of return to preinjury level sport (83%) but with decreased performance 13,14 whereas recreational athletes show a low return rate after 1 year 15 . The rate of return to the same preinjury‐level of sports participation may be higher in athletes with high motivation and excellent resources such as professional athletes 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…The rate of return to sport is higher in athletes younger than 19 years, at all levels of participation 12 . Elite athletes show the highest rate of return to preinjury level sport (83%) but with decreased performance 13,14 whereas recreational athletes show a low return rate after 1 year 15 . The rate of return to the same preinjury‐level of sports participation may be higher in athletes with high motivation and excellent resources such as professional athletes 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the hop test is a widely used tool to assess the functional capacity of the lower limb, requesting a propulsive action to perform a horizontal jump and landing 7 . Its results have a functional implication, since they are useful in predicting the risk of lower limb injuries 8 , detecting functional improvements 9 , and guiding return-to sport decisions 10 . The study of its psychometric properties has demonstrated that it is a valid and reliable tool for functional assessment 11 , 12 , which has led to its recommended used in the field of sports in the context of both prevention and recovery from injuries 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the hop test is a widely used tool to assess the functional capacity of the lower limb, requesting a propulsive action to perform a horizontal jump and landing 7 . Its results have a functional implication, since they are useful in predicting the risk of lower limb injuries 8 , detecting functional improvements 9 , and guiding return-to sport decisions 10 . The study of OPEN 1 Exercise Intervention for Health Research Group (EXINH-RG), Department of Physiotherapy, University of Valencia, Calle Gascó Oliag 5, 46010 Valencia, Spain.…”
mentioning
confidence: 99%
“…Indeed, the hop test is a widely used tool to assess the functional capacity of the lower limb, requesting a propulsive action to perform a horizontal jump and landing [7]. Its results have a functional implication, since they are useful in predicting the risk of lower limb injuries [8], detecting functional improvements [9], and guiding return-to sport decisions [10]. The study of its psychometric properties has demonstrated that it is a valid and reliable tool for functional assessment [11,12], which has led to its recommended used in the eld of sports in the context of both prevention and recovery from injuries [7].…”
Section: Introductionmentioning
confidence: 99%